Stepping in Place While Voluntarily Turning Around Produces a Long-Lasting Posteffect Consisting in Inadvertent Turning While Stepping Eyes Closed - Stefania Sozzi; Marco Schieppati (Neural Plasticity)
Training subjects to step in place on a rotating platform while maintaining a fixed body orientation in space produces a posteffect consisting in inadvertent turning around while stepping in place eyes closed (podokinetic after-rotation, PKAR). We tested the hypothesis that voluntary turning around while stepping in place also produces a posteffect similar to PKAR. Sixteen subjects performed 12 min of voluntary turning while stepping around their vertical axis eyes closed and 12 min of stepping in place eyes open on the center of a platform rotating at 60°/s (pretests). Then, subjects continued stepping in place eyes closed for at least 10 min (posteffect). We recorded the positions of markers fixed to head, shoulder, and feet. The posteffect of voluntary turning shared all features of PKAR. Time decay of angular velocity, stepping cadence, head acceleration, and ratio of angular velocity after to angular velocity before were similar between both protocols. Both postrotations took place inadvertently. The posteffects are possibly dependent on the repeated voluntary contraction of leg and foot intrarotating pelvic muscles that rotate the trunk over the stance foot, a synergy common to both protocols. We propose that stepping in place and voluntary turning can be a scheme ancillary to the rotating platform for training body segment coordination in patients with impairment of turning synergies of various origin.